Inclusive Education And The Rights Of Differently-Abled Children Under The Rte Act, 2009 And The Rpwd Act, 2016 - Sahu, Manya (Trinity Law Review, 2026)
Inclusive education is both a legal mandate and a moral imperative in modern democratic societies. In India, the rights of differently-abled children have evolved significantly over the past three decades, particularly through the enactment of the Right of Children to Free and Compulsory Education Act, 2009 (RTE Act) and the Rights of Persons with Disabilities Act, 2016 (RPwD Act). The two legislations, when read together with constitutional provisions under Articles 14, 15, 21, 21A, 41 and 46, embody a vision of education that is equitable, barrier-free, and nondiscriminatory. Yet, the ground realities of infrastructure, teacher preparedness, budgetary allocation, and persistent social stigma reveal a paradoxical gap between law and practice. This paper undertakes a doctrinal and socio-legal study of inclusive education in India. It critically analyses statutory provisions, judicial interpretations by the Supreme Court and High Courts, and empirical data from the Census of India (2011), NSSO surveys, UDISE+ reports, NCERT studies, and UNICEF situational analyses. The findings demonstrate that although India has established a robust legislative framework, implementation challenges have resulted in disproportionately low enrollment and high dropout rates among differently-abled children. For instance, while the national literacy rate stands at 74%, the literacy rate for persons with disabilities is only 59.29%; similarly, dropout rates among disabled children remain nearly three times higher than those of their peers. The study also situates India’s progress within the international legal framework, especially the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) and the Salamanca Statement (1994), both of which emphasise inclusive education as a fundamental human right. Comparative insights from jurisdictions like South Africa, Finland, and Canada provide useful models for strengthening India’s inclusive education ecosystem. Ultimately, the research concludes that inclusive education is not merely a legal right but a constitutional necessity and a precondition for realizing substantive equality. To bridge the gap between law and practice, India must strengthen teacher training, expand budgetary allocations, modernize infrastructure, and mainstream anti stigma initiatives. Without these, the promises of the RTE Act and RPwD Act risk remaining aspirational rather than transformative.